Tribes as Non-State Actors in the Arab Monarchies of the Persian Gulf at the Present Stage (the Case of the UAE) - A. К. Adrianov (Международная аналитика)
The article examines the tribal structures of the UAE as non-state actors. The author pays special attention to the definition of the concept of “tribe” in the Arab world and its interpretation in relation to the countries of the Persian Gulf and, in particular, the UAE as one of the most complex tribal systems in the region. It explores the question of tribal identity and its manifestations at the present stage, as well as its influence on the position of tribes as political actors. Based on the classification of non-state actors by Vitaliy Naumkin and Vasiliy Kuznetsov, the author examines the tribe as a local and state-oriented actor. Three situations are identified in which the tribe as an actor can manifest itself most clearly. The author concludes that tribes cannot be considered as fully-fledged non-state actors, but that they retain significant potential for mobilisation and political action in crisis situations.